Cationic Bis‐N‐Heterocyclic Carbene (NHC) Ruthenium Complex: Structure and Application as Latent Catalyst in Olefin Metathesis. Issue 42 (11th September 2014) - Rouen, Mathieu; Queval, Pierre; Falivene, Laura; Allard, Jessica; Toupet, Loïc; Crévisy, Christophe; Caijo, Frédéric; Baslé, Olivier; Cavallo, Luigi; Mauduit, Marc
Abstract: An unexpected cationic bis‐N‐heterocyclic carbene (NHC) benzylidene ether based ruthenium complex (2 a ) was prepared through the double incorporation of an unsymmetrical unsaturated N‐heterocyclic carbene (U2 ‐NHC) ligand that bore an N‐substituted cyclododecyl side chain. The isolation and full characterization (including X‐ray diffraction studies) of key synthetic intermediates along with theoretical calculations allowed us to understand the mechanism of the overall cationization process. Finally, the newly developed complex2 a displayed interesting latent behavior during ring‐closing metathesis, which could be "switched on" under acidic conditions. Abstract : Double U : A cationic bis‐N‐heterocyclic carbene (NHC) benzylidene ether based Ru complex was prepared by double incorporation of the unsymmetrical unsaturated NHC ligand (see scheme). Characterization of key synthetic intermediates along with theoretical calculations allowed us to understand the mechanism of the cationization step. Finally, the newly developed cationic complex displayed interesting latent behavior during ring‐closing metathesis, which could be "switched on" under acidic conditions.